The Influence of Organizational Motivation and Commitment on Employee Retention in the Educational Services Sector at the University Level - Kusumah, Anuraga; Wibowo, Agung; Prasetya, Angga (Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the influence of work motivation and organizational commitment on employee retention in the education service sector. In an era of competition and increasingly high dynamics in the world of work, educational institutions face great challenges in retaining qualified educators and administrative staff. This study uses a quantitative approach by distributing questionnaires to 75 respondents from educators and administrative staff at Ibn Khaldun University. The results of multiple regression analysis showed that both work motivation and organizational commitment had a positive and significant effect on employees' decisions to stay at the institution. This study provides practical recommendations for education management in developing strategies to increase HR motivation and loyalty